Primary Education Teacher Training: an exploratory study from the lockdown towards the post Covid period - Eugenia Di Barbora; Lucia Bragatto; Lucia Locuoco; Daniela Paci; Maura Tavano (Firenze University Press, 2021)
This exploratory study, conducted during the first Covid-19 lockdown, formed part of the practical module of the Teacher Training in Primary Education course at the University of Udine, and was carried out on a sample of trainees enrolled on the course. The research had the following objectives: to understand the effects of the Covid-19 lockdown on trainees and to reflect on the impact on planning of teaching in a traditional classroom environment or in VLE, Virtual Learning Environment. In order to improve the practical components of the course, observations focused on organizational, methodological and pedagogical aspects. The data, gathered in an online questionnaire, provided a comparison of teacher training delivered in person in the pre-Covid period and in later training online. The data also provided information on the strengths and weaknesses of classroom and distance learning, on the use of technology and on the professional development of teachers in the future. The study found a multitude of issues that will need to be further explored in the post Covid period, including rethinking models and approaches in initial teacher training.    Tirocinio di Scienze della Formazione Primaria: uno studio esplorativo nel primo lockdown per Covid.   Il presente studio esplorativo è stato promosso, durante il primo lockdown per Covid-19, all'interno del Tirocinio del Corso di Studi in Scienze della Formazione Primaria dell'Università di Udine su un campione di studenti iscritti al tirocinio. La ricerca esplorativa ha avuto come obiettivi: comprendere le ricadute nei tirocinanti conseguenti allo stato di emergenza e riflettere sulla didattica in presenza e a distanza sui piani organizzativo, metodologico e pedagogico per potenziare l'offerta formativa del tirocinio. I dati, desunti da un questionario online, hanno permesso un confronto sul tirocinio in presenza nel periodo pre-Covid e successivamente svolto in DaD. I dati hanno fornito anche risultati su punti di forza e criticità della didattica in presenza e a distanza, sull'uso delle tecnologie e sulla professionalità docente futura. Lo studio ha inoltre rilevato una molteplicità di aspetti che andranno ulteriormente approfonditi per il periodo post Covid-19, tra cui il ripensamento di modelli ed approcci nella formazione iniziale degli insegnanti.